SILIKA BEBAS NATRIUM DARI LIMBAH SEKAM PADI SEBAGAI BAHAN DASAR PEMBUATAN MINERAL TRIOXIDE AGGREGATE - Leny Yuliatun; Anissa Riyawati; Nuryono (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2019)
One of the basic ingredients of making White Mineral Trioxide Aggregate (MTA) was silica. The sources of silica was from white rice husk ash (RHA) and silica extracted from RHA. Silica could be extracted from natural ingredients in the form of rice husk ash. The purpose of this study were to extract silica from rice husk ash and purify the silica extracted by washing using distilled water to free sodium, so that it could be used as the basic ingredient in making MTA. Sodium was a hygroscopic metal that could cause the presence of pores in MTA material if applied to the teeth. The amount of washing volume varies to a certain volume which indicates that silica was free Na. Based on the results of the experiment it could be concluded that the washing of silica by stirring with distilled water would produce free Na silica by washing 450 mL. This wasnot proven at peak 2θ (300), as well as proof of the presence of silanol and siloxane groups before and after washing with FTIR spectroscopy. In addition, the washing volume also affects the intensity of the –OH peak in wave numbers 1635,64 cm-1 the more volume used, the intensity of the –OH group increases, so that the water hydrated in silica also increases. Silica free Na would be used as the starting material for making MTA which was applied to teeth medicament or root canal treatment.